A study on prevalence of myopia among high school children in an urban area of Shivamogga: a cross sectional study - Kotabal, Rajashree; Belur, Mangala N.; C., Nandini; Nagendra, Kanchan (International Journal Of Community Medicine And Public Health, 2017)
Background:Blindness is one of the significant social problem in India with uncorrected refractive error as the second major cause accounting for 19.7% of the blindness. Prevalence of myopia in children varies between the countries and it ranges from 7% to 30%. Among all refractive problems myopia is the major cause of disability in children. The objective of the study was to determine the prevalence and causes of myopia among high school children. Methods:This study was a descriptive Cross sectional study. Present study was conducted among high-school children of 13 - 16 years in an urban area of Shivamogga city of Karnataka state from July- August 2015. With expected frequency of 20%, confidence limit at 5% and confidence level at 95% the total sample size was 246. A pretested questionnaire was used for collection of data. Snellen’s chart was used to find out the myopia. Results: The overall prevalence of myopia was found to be 23%. Out of 300 students 16%, 5%, and 1.7% of the students had mild, moderate and sever visual impairment respectively. Conclusions:The prevalence of myopia was higher among high school children in urban area and it was more among girls than the boys. Early diagnosis and correction of the refractive error has to be done to prevent future development of blindness.